2018
DOI: 10.1186/s12989-018-0268-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent cyto- and genotoxicity of nickel metal and nickel oxide nanoparticles in human lung cells

Abstract: BackgroundGenotoxicity is an important toxicological endpoint due to the link to diseases such as cancer. Therefore, an increased understanding regarding genotoxicity and underlying mechanisms is needed for assessing the risk with exposure to nanoparticles (NPs). The aim of this study was to perform an in-depth investigation regarding the genotoxicity of well-characterized Ni and NiO NPs in human bronchial epithelial BEAS-2B cells and to discern possible mechanisms. Comparisons were made with NiCl2 in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 54 publications
5
74
0
Order By: Relevance
“…Consequently, the intensity of the scattered light increases in a non-linear manner with increasing size and number of particles in the dispersion and decreases with particle sedimentation and dissolution. 7,20 Our results showed that the 10 nm particles and 75 nm particles displayed a more pronounced sedimentation in serum-free cell culture medium when compared to medium supplemented with 10% FBS (Fig. 1A-F).…”
mentioning
confidence: 71%
“…Consequently, the intensity of the scattered light increases in a non-linear manner with increasing size and number of particles in the dispersion and decreases with particle sedimentation and dissolution. 7,20 Our results showed that the 10 nm particles and 75 nm particles displayed a more pronounced sedimentation in serum-free cell culture medium when compared to medium supplemented with 10% FBS (Fig. 1A-F).…”
mentioning
confidence: 71%
“…Hydrodynamic size distribution and zeta potential of NP suspensions (50 µg/mL) in water and two different cell culture media (see below) was measured at 1 and 24 hours by dynamic light scattering (DLS) using a Malvern Zetasizer Nano ZS instrument equipped with 4.0 mW, 633 nm laser (Model ZEN3600, Malvern Instruments Ltd., UK) as described . NP stability and sedimentation in cell media was determined by photon cross‐correlation spectroscopy (PCCS) . In brief, PCCS (NanoPhox, Sympatec) was used to analyze NP dispersions (50 μg/mL) immediately after dispersion (5 minutes), and after 1 and 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The prolonged 980 nm excitation resulted in an increasedp hototoxicity effect measured by proliferation MTT assay commonly applied to evaluate cell sensitivity or cell death after photodynamic protocols [61,62] (Figure5d). The DCF-assay is ac ommonly applied and verified methodt oe stimate an immediate release of free radicals [63,64] and gives similars ensitivity to other ROS indicative methods based on molecular probes, for example, the H 2 DCF-DAr eagent. In the case of NCs loaded only by VP no significant differences were noticeable after irradiation.…”
Section: Fret-based Interaction Between Ucnps and Vp Moleculesmentioning
confidence: 96%